Accidental exposure to blood (AEB), a real public health problem for medical and paramedical staff at the university hospital of mostaganem - Bestaoui, S.; Amar, NH.; Bouhalloufa, H. F (International Journal of Medicine, 2024)
Accidents involving exposure to free and bodily fluids are a real problem for health professionals, especially paramedics. Several factors aggravate this situation, including the lack of protective vaccination, neglect of protective measures, overwork, e.g. The aim of our study was to identify the number of cases of AEB in the working population, as well as the main causes leading to this.This is a retrospective study on the records of patients declared victims of AEB in the infectious diseases department of the Mostaganem University Hospital from January 2022 to December 2023. Inclusion criteria: HIV-negative patients. Have a viral load in the first month for HIV. Known vaccination status for HBS.Forty-four patients were identified, with a predominance of more than 68% among nurses, The hollow needle was the most frequent source of contamination in 50% of cases, and the department most at risk of these accidents was medical-surgical emergencies, Overexertion was found in 48%, as well as the absence of hepatitis B vaccination, the virological status of the source was unknown in 46% of cases, ARVs were adhered to for 28 days in 85% of cases.Exposure to blood has become one of the major problems in healthcare settings for paramedics especially, with hollow needle sticks remaining the leading cause as well as blood splashes. Even if the causes are well known and the conduct to be followed is well codified, these accidents are most often neglected and largely underreported. As a result, management is delayed and may expose patients to the risk of seroconversion for HIV, HCV, HBS.